Mechanistic Insights into Annulation of Arylidene‐Δ2‐Pyrrolin‐4‐Ones by Cinchona Squaramide‐Based Organocatalysts. Issue 5 (27th January 2022) - Ciber, Luka; Ričko, Sebastijan; Gregorc, Jure; Požgan, Franc; Svete, Jurij; Brodnik, Helena; Štefane, Bogdan; Grošelj, Uroš
Abstract: Arylidene‐Δ 2 ‐pyrrolin‐4‐ones undergo organocatalyzed annulation with malononitrile, furnishing dihydropyrano[3, 2‐ b ]pyrroles (18 examples, 0–77% ee in dichloromethane, 11–44% ee in methanol). The products could be enantiomerically enriched by trituration (11 examples, 95–99% ee). Enantioselectivity was dependent on the nature of the substrate and the conformation of the catalyst, which in turn was solvent‐controlled. The reaction mechanism, which included two pseudo‐enantiomeric organocatalyst conformations, was investigated by experimental and quantum chemical methods. The reaction mechanism consists of Michael addition reaction step followed by 6‐ exo ‐ dig annulation, which was found to be the rate determining step. Additionally, it was identified that the preferred reaction pathway follows the model originally proposed by Pápai et al. Abstract :